Profile of Open Cholecystectomy at Dr. Moewardi Hospital Surakarta January 2016 – December 2017 (Retrospective Study) - Rakhman Wahyudi Mulyo; Agus Rahardjo; Muhammad David Perdana Putra; Rico Alfredo Hutabarat; Pigur Agus Marwanto (HM Publisher, 2021)
Background. Cholelithiasis is a disease found in the general population throughout the world, and is influenced by several factors such as gender, age, and Body Mass Index. Gallstone disease is a common indication for surgery. The surgical procedure can be done in 2 ways, with an open cholecystectomy or laparoscopic cholecystectomy.Methods. This study was conducted on patients who were treated at the Regional General Hospital dr. Moewardi Surakarta from January 2016 to December 2017 with retrospective sampling. The patient's age, gender, weight, height, and length of stay were taken based on the data listed in the patient's medical record.Results. A total of 96 patients, consisting of 61 (63.54%) women and 35 (36.46%) men who met the criteria for inclusion in this study. The age of the patients ranged from 31 to 86 years with a mean of 52.16 years. According to the age category, namely <40 years and 40 years, there were 14 (14.58%) and 82 (85.42%) people from all respondents, respectively. Only 26 (27.1%) obese patients were found in this study. The mean length of post-operative hospitalization was 6.69 ± 3.47 days.Conclusion. Gender and length of post-operative hospitalization in this study have characteristics that are in accordance with several previous studies.